Association between bh4/bh2 ratio and Albuminuria in Hypertensive Type -2 Diabetic patients - Aviles-Herrera, Jose; Arana-Pazos, Karla C; Valle-Mondragon, Leonardo Del; Guerrero-García, Carolina; Rubio-Guerra, Alberto Francisco (Journal of Clinical Nephrology, 2017)
Endothelial dysfunction and inflammation play a key role in the pathophysiology of diabetic nephropathy; Tetrahydrobiopterin (BH4) is an essential cofactor for nitric oxide synthase, when BH4 is reduced to dihydrobiopterin (BH2), endothelial dysfunction is induced. Purpose: The aim of this study is to evaluate the relationship between the levels of biopterins with albuminuria in type-2 diabetic hypertensive patients. Methods: We studied 30 hypertensive type-2 diabetic patients in whom biopterins levels were measured by reverse phase high performance liquid chromatography with fluorescence detection. Additionally, 24 h urinary albumin excretion was also measured (nephelometry). The levels of biopterins and albuminuria were correlated with the Pearson correlation coefficient. Results: We did not find a significantly correlation between biopterins levels and albuminuria, However, we found a significantly inverse correlation (R= -0.498, p<0.005) between the BH4/BH2 ratio and albuminuria. Conclusion: Our results suggest that the BH4/BH2 ratio instead of biopterins levels may be a marker of nephropathy in hypertensive type-2 diabetic patients.